DETERMINATION OF OIL RECOVERY FACTOR BY USING WATER INJECTION-LABORATORY TEST METHOD - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2005)
Oil production limit that is usually followed by decrease of oil productivity in old fields is a major problem and can't be avoided. This case happened when cumulative oil production has approached primary recovery method. Decrease of the action of native reservoir energy is followed by drastically increase of production of water (saturation almost 100 %). In relation to this, a method is needed to obtain the additional oil recovery. Water injection method is one of the solutions to solve oil production problem that happened in old fields. It is expected that by using water injection method, productivity and oil recovery in old fields can be improved. Water that is used as the fluid injected into reservoir to improve oil recovery is sea water. How far oil recovery can be improved by using water injection method, is determined by a laboratory research. Before carrying out water injection laboratory test; one has to know what the main points that play important role in determining the optimal oil recovery by water injection method. These are: firstly, reservoir data, secondly, formation water and sea water analysis, thirdly, determination of physical fluid and rock properties, next, the displacement of water injection process to obtain the additional oil recovery and standard operational procedure. The main focus of this paper is